How do we study the blogosphere? Research and methods of assessing the impact of blogging on the public sphere - Kyza, Eleni A.; Milioni, Dimitra L. (My University, 2009)
The main aim of this paper is to revisit and assess our research methods and findings regarding the impact of blogging on the public sphere. In the first part of the study, we review existing literature on blogging, identifying the type of research questions being asked and the results that blogging research has yielded so far, both in local and international and/or comparative contexts. In the second part of the study, we review existing methods for researching blogging and the available analytical and software tools, discussing the methodological constraints that keep us from delving into the impact of blogging on mainstream media and democracy. Particular emphasis is given on the challenges that arise when researching blogospheres of not widely spoken languages.
Keywords: Blogging; Public sphere; Meta-analysis; Research methodology